Deep Breathing Relaxation Techniques to Lowering Systolic Blood Pressure in the Elderly: Randomized Control Trial - Novian Mahayu Adiutama; Hera Hijriani; Wawan Kurniawan; Wardah Fauziah; Chiou - Feng Lin (Journal Of Nursing Practice, 2022)
Background: Continuous high blood pressure causes the heart to work extra hard, eventually this condition results in damage to the blood vessels of the heart, kidneys, brain, and eyes. Hypertension management is recommended to minimize pharmacological therapy with the aim of avoiding side effects. Non-pharmacological efforts that can be done in patients with hypertension are by controlling various aspects such as deep breathing techniques. Purpose: This study aims to determine the effect of deep breathing relaxation techniques to reducing blood pressure in the elderly with hypertension. Quasy-experiment pre-post-test with control group was conducted on 108 elderlies with hypertension at a Puskesmas located in Subang with simple random sampling technique. Methods: This study was conducted by providing deep breathing techniques to the elderly in the treatment group for 3 months. The statistical test used was the independent t test and chi-square. Results: The deep breathing relaxation technique given at a dose of 15 minutes 3 times a day for 3 months has been shown to have an effect on reducing blood pressure in the elderly. Conclusion: Future research can conduct research on deep breathing by paying more attention to confounding variables such as stress, anxiety, and diet.